Analysis of Elementary School Teachers' Understanding of the Implementation of the Minimum Competency Assessment (AKM) Policy - Jaenudin, Irfan; Kurniasih, Dwi; Ulfah, Sri Wahyuni; Robandi, Babang (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
Teachers have an important role in successfully implementing AKM policies in elementary schools. This study aims to describe the level of understanding of elementary school teachers regarding implementing the AKM policy. Through a quantitative approach with the survey method, data is collected using a questionnaire via Google Forms. The instrument was validated with content validity by experts and test-retest reliability to test its reliability. The data obtained were then analyzed using descriptive statistics in the form of percentages. The procedure for carrying out this survey research begins with formulating the research problem and objectives, identifying research subjects, selecting data collection techniques, making instruments, distributing instruments, and analyzing data and reporting. There were 113 research samples from the population of 392 elementary school teachers in Megamendung District, Bogor Regency. The results of this study indicate that the average percentage of elementary school teachers' understanding of the implementation of the AKM policy is 71% or in the good category. Based on these data, it can be seen that elementary school teachers in Megamendung District, Bogor Regency, understand the concept of implementing the AKM policy set and socialized by the Ministry of Education and Culture of the Republic of Indonesia.